Tanjong life the new norm - Mohd Azmi Mohd Hussin
Penang-born cartoonist Azmi Hussin captures the pandemic stories of Penangites the way he knows best - through comics! Tanjong Life: The New Norm follows the funny adventures of Joe G - Azmi's buck-toothed, true-blue Penangite character - as he explores the amusing and the not-so-amusing sides of the new normal, highlighting everything from getting caught up in the Dalgona coffee craze to getting his body temperature checked before riding a trishaw, watching performing arts online and finding out what improperly disposed face masks can do. Sure, the pandemic is tough on all of us, but Joe G has undoubtedly found hilarious ways to live life to the fullest in Penang's new normal!